Requirement of the agr Locus for Colony Spreading of Staphylococcus aureus - Tsompanidou, Eleni (American Society for Microbiology (ASM), 2011)
The important human pathogen Staphylococcus aureus is known to spread on soft agar plates. Here, we show that colony spreading of S. aureus involves the agr quorum-sensing system. This finding can be related to the agr-dependent expression of biosurfactants, such as phenol-soluble modulins, suggesting a connection between spreading motility and virulence.